dfAugmented renal clearance in critically ill trauma patients admitted to Chris Hani Baragwanath Academic Hospital Intensive Care Unit: a retrospective review of data - Mafuya, Zoleka (My University, 2020)
Augmented renal clearance (ARC) is enhanced elimination of solutes by the kidneys. Patients with ARC have normal plasma creatinine concentrations and typically display a hyperdynamic circulation, with increased cardiac output, resulting in renal hyper-perfusion and increased creatinine clearance (CrCl). The resultant enhanced elimination of renally cleared agents may be associated with sub-therapeutic drug levels and lower minimum inhibitory concentration of antibiotics. There is a paucity of studies describing the occurrence and features of ARC in a South African population. Methods We conducted a retrospective review of data of all trauma patients admitted to the Intensive Care Unit (ICU) at Chris Hani Baragwanath Academic Hospital (CHBAH) during a one-year period to identify those with features of ARC. Results- Of the 96 trauma patients admitted to CHBAH ICU over the study period, 38 met inclusion criteria. Of these, 29 showed features of ARC (CrCl > (130mL/min/1.73 m2). Most patients with ARC were male 75.9% (n=22/29), with a mean age of 32.7 years (SD 11.3 years) and mean weight of 75.7 kg (SD 14.0). Overall, 76.3% (n=29/38) of patients had at least 1 episode of ARC during the first 7 days of ICU admission. CrCl was highest on day 4 occurring in 77.8% (n=14/18) of patients with an average CrCl of 180 ml/min/1.73m2 and again at day 7 in 77.8% of patients with an average CrCl of 163 ml/min/1.73m2 The majority of those with ARC 86.2% (n=31) had undergone emergency surgery on admission, and 25% (n=9) had required inotropic support during their ICU stay. There was no significant difference in modified Sequential Organ Failure Assessment (p=0.836), Acute Physiology and Chronic Health Evaluation (p=0.081), or Injury Severity Scores (p=0.422) between patients with ARC and those with no features of ARC. Conclusion A high prevalence of ARC was detected in our South African ICU population. As this was a single centre, retrospective audit, with a limited sample size, further studies exploring the presence and clinical impact of ARC in the South African trauma population and in other populations are still needed.
A research report submitted in fulfillment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020